Motor performance deterioration accelerates after 50 years of age in Charcot‐Marie‐Tooth type 1A patients. (14th December 2017) - Tozza, S.; Bruzzese, D.; Pisciotta, C.; Iodice, R.; Esposito, M.; Dubbioso, R.; Ruggiero, L.; Topa, A.; Spina, E.; Santoro, L.; Manganelli, F.
Abstract : Background and purpose: The aim of our study was to describe, by a case‐control and cross‐sectional design, the correlation between clinical impairment and age in Charcot‐Marie‐Tooth type 1A (CMT1A) patients. Methods: Seventy CMT1A patients and 70 sex‐ and age‐matched healthy controls were enrolled. Motor performance was assessed through the 10‐m walk test, the 6‐min walk test and the 9‐hole peg test of the dominant and non‐dominant side, and muscle strength was measured by using the Medical Research Council score. In the CMT1A group, disability and quality of life were evaluated using the Charcot‐Marie‐Tooth Neuropathy Score (CMTNS) and the Short Form 36 (SF‐36) questionnaire. Cross‐sectional relationships between age and all clinical measures were analyzed and differences in the slopes between cases and controls were calculated. The occurrence of a structural change in the age‐related progression of clinical measures was explored. Results: The deterioration of motor performance correlated with age in both groups with a greater slope in CMT1A patients than controls. The deterioration of CMTNS and SF‐36 correlated with age in the CMT1A group. The deterioration of all clinical measures with the exception of the SF‐36 questionnaire showed a structural change at the 50th year of age. The rate of deterioration was no different between patients and controls until 50 years of age, whereupon it became significantly greater in CMT1A patients. Conclusion: Our study supports that the disease progression in CMT1A patients is an age‐related process and the 50th year of age represents a critical moment after which the clinical decline becomes faster.